In the distance - Díaz, Hernán, 1973- (Coffee House Press, 2017)
"A young Swedish boy finds himself in penniless and alone in California. He travels East in search of his brother, moving on foot against the great push to the West. Driven back over and over again on his journey through vast expanses, Håkan meets naturalists, criminals, religious fanatics, Indians, and lawmen, and his exploits turn him into a legend. Diaz defies the conventions of historical fiction and genre (travel narratives, the bildungsroman, nature writing, the Western), offering a probing look at the stereotypes that populate our past and a portrait of radical foreignness. At first, it was a contest, but in time the beasts understood that, with an embrace and the slightest push, they had to lie down on their side and stay until Håkan got up. He did this each time he thought he spied someone on the circular horizon. Had Håkan and his animals ever been spotted, the distant travelers would have taken the vanishing silhouettes for a mirage. But there were no such travelers-the moving shadows he saw almost every day in the distance were illusions. With the double intention of getting away from the trail and the cold, he had traveled south for days. Hernan Diaz is the author of Borges, Between History and Eternity (Bloomsbury 2012), managing editor of RHM, and associate director of the Hispanic Institute at Columbia University. He lives in New York"--